THE ANTHROPOMORPHIC-BASED CHARACTER IN THE ANIMATION FILM “AYO MAKAN SAYUR DAN BUAH” - Pebriyanto, Pebriyanto; Ahmad, Hafiz Aziz; Irfansyah, Irfansyah (Seni Media Rekam ISI Surakarta, 2022)
Children are arguably less motivated to consume vegetables. At the same time, animated films as learning media are considered effective in evoking emotion and influencing the audience. Consequently, the Ministry of Health of the Republic of Indonesia created the animated film